Characterization of the Thermal Behavior of the Full Scale Testing Module, Using 17.5% of Glazing with Different Orientations in Mexico City. - SÃ¡nchez B, Ricardo; S. Ahmad, Sabarinah; B. Zeevaert, Leonardo; Valeriano F, Arturo (International Journal of Engineering and Technology, 2018)
The study aims to understand the thermal performance behavior of a double skin envelope system in a test cell.Â A rooftop observation deck and experimentation laboratory is installed at the â€œJâ€ Building of the Postgraduate Unit, National Autonomous University of Mexico campus (19Â°18â€™33.59â€N, 99Â°11â€™5.73â€O).Â This platform consists of two full-scale testing modules. Each cubic module measures 3m x 3m x 3m.Â All of its facades have several layers of insulation.Â This platform was designed to test materials and construction systems under the Mexico City microclimate.Â It is possible to measure thermal, lighting, acoustic and indoor air quality variables. Mexico City building codes indicate that the minimum span to be used in a room must be at least 17.5% of the area of the room.Â Using the Experimentation FaÃ§ade, which allows us to observe all available orientations; we place a window with these characteristics and measure its thermal behavior in each of the orientations.Â The results obtained allowed us to identify that the window when observing the North or South orientations does not greatly increase the internal temperature of the Module.Â On the other hand, when the window observes the orientations East and West, the internal temperature increase, establishes conditions of inhabitability inside the Module, recording temperatures of above 50Â°C.Â Â